Penggunaan Aplikasi Sepran : Studi Kasus Usaha Thrift Sandangcuan Blitar - Intan Rorencia (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Recording of income in the Blitar Used Goods business is still done manually. Financial records are still not well organized, they are still limited to notes in Notepad, an application on a smartphone. Revenue earned from this business is recorded based on the results received from direct sales, while those through online or e-commerce platforms are often not recorded. So the owner cannot know exactly how much income he receives per month. This is the background for using the Sepran application because the features presented are simpler, according to the needs of business owners. The Sepran application can be used without using an internet network, it is easy to understand and the application operation is simple. The purpose of this research is to provide a way to use the Sepran application to record business income. The type of research used is descriptive with interview and observation techniques. The results of this study are the stages of recording income using the Sepran Application starting from account registration to entering transactions into the receipt feature